A prática do parto humanizado no SUS: estudo comparativo = The practice of humanized delivery in the Brazilian Health System (SUS): a comparative study - Luciele de Lima Wrobel; Sueli Terezinha Martins Ribeiro (Universidade Estadual de Maringá, 2006)
O presente estudo descritivo foi realizado em maternidades que prestamatendimento pelo Sistema Único de Saúde (SUS), nas cidades de Guarapuava e Londrina, Estado do Paraná. Dentro do programa de Humanização implantado na Maternidade de Londrina pretendeu-se analisar o atendimento a parturiente quanto à humanização ao partocomparando com a realidade de dois hospitais de Guarapuava onde não existe o programa implantado e assim verificar se os direitos destas parturientes quanto à humanização estão sendo respeitados. Foi aplicado um questionário a 40 primíparas no puerpério imediato comperguntas semi-estruturadas. Ao comparar duas realidades diferentes, concluiu-se que alguns dos direitos das parturientes preconizados pela OMS não estavam sendo respeitados, especialmente onde não havia a implantação do parto humanizado, pois não era permitida a entrada de acompanhante e nem utilizadas técnicas de relaxamento para a parturiente, evidenciando assim que algumas instituições necessitam intensificar esses cuidados para melhorar a qualidade do atendimento prestado. This descriptive study was conducted in maternities assisted by the Brazilian Health System (SUS), in the cities of Guarapuava and Londrina, State of Paraná. In the program implanted in Londrina, the aim was to analyze the assistance to the parturient regarding humanization to the child delivery. This context was then comparedwith the reality in the maternities of two hospitals in Guarapuava, where these practices are not applied. The comparison intended to verify if the rights of these women to humanized delivery are being respected. A half-structured questionnaire was applied to forty women in labor. While comparing these two different realities, it was observed that a few of these rights, advocated by the OMS, were not being respected, especially where the humanization delivery was not a practice. Data revealed that the partner's entrance was not allowed,neither were put into practice the parturient relaxation techniques, which evidenced that some institutions need to intensify these kinds of care in order to improve the quality of the assistance provided.